Genetic Divergence of Lineage-Specific Tandemly Duplicated Gene Clusters in Four Diploid Potato Genotypes - Bonthala, Venkata Suresh; Stich, Benjamin (Frontiers in Plant Science, 2022)
Potato (Solanum tuberosum L.) is the most important non-grain food crop. Tandem duplication significantly contributes to genome evolution. The objectives of this study were to (i) identify tandemly duplicated genes and compare their genomic distributions across potato genotypes, (ii) investigate the bias in functional specificities, (iii) explore the relationships among coding sequence, promoter and expression divergences associated with tandemly duplicated genes, (iv) examine the role of tandem duplication in generating and expanding lineage-specific gene families, (v) investigate the evolutionary forces affecting tandemly duplicated genes, and (vi) assess the similarities and differences with respect to above mentioned aspects between cultivated genotypes and their wild-relative. In this study, we used well-annotated and chromosome-scale de novo genome assemblies of multiple potato genotypes. Our results showed that tandemly duplicated genes are abundant and dispersed through the genome. We found that several functional specificities, such as disease resistance, stress-tolerance, and biosynthetic pathways of tandemly duplicated genes were differentially enriched across multiple potato genomes. Our results indicated the existence of a significant correlation among expression, promoter, and protein divergences in tandemly duplicated genes. We found about one fourth of tandemly duplicated gene clusters as lineage-specific among multiple potato genomes, and these tended to localize toward centromeres and revealed distinct selection signatures and expression patterns. Furthermore, our results showed that a majority of duplicated genes were retained through sub-functionalization followed by genetic redundancy, while only a small fraction of duplicated genes was retained though neo-functionalization. The lineage-specific expansion of gene families by tandem duplication coupled with functional bias might have significantly contributed to potato’s genotypic diversity, and, thus, to adaption to environmental stimuli.